2022
DOI: 10.3390/microorganisms10050939
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic Bacterial Diversity of Corn Leaf Aphid, Rhopalosiphum maidis Fitch (Hemiptera: Aphididae) Associated with Maize Management Systems

Abstract: In this study, different maize fields cultivated under different management systems were sampled to test corn leaf aphid, Rhopalosiphum maidis, populations in terms of total and endosymbiotic bacterial diversity. Corn leaf aphid natural populations were collected from traditionally managed maize fields grown under high agricultural and natural landscape diversity as well as conventionally treated high-input agricultural fields grown in monoculture and with fertilizers use, hence with low natural landscape dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…To decode the functional implications of these gut symbionts, it is necessary to study their distribution. Thus, we have summarized recent metagenomics studies (whole insect and insect gut) of several insect pests which is demonstrated by phylum wise composition of bacteria in Figure 1A ( Yong et al, 2017 ; Tokuda et al, 2018 ; Bozorov et al, 2019 ; Gawande et al, 2019 ; Shah et al, 2020 ; Asimakis et al, 2021 ; Deguenon et al, 2021 ; He et al, 2021 ; Tegtmeier et al, 2021 ; Yu et al, 2021 ; Csorba et al, 2022 ; Li S. et al, 2022 ; Majumder et al, 2022 ; Wang et al, 2022 ). We have noticed with taken examples that Proteobacteria, Firmicutes and Actinobacteria were the most dominant phyla present in the insect gut could be due to their diverse roles in nutrition.…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%
“…To decode the functional implications of these gut symbionts, it is necessary to study their distribution. Thus, we have summarized recent metagenomics studies (whole insect and insect gut) of several insect pests which is demonstrated by phylum wise composition of bacteria in Figure 1A ( Yong et al, 2017 ; Tokuda et al, 2018 ; Bozorov et al, 2019 ; Gawande et al, 2019 ; Shah et al, 2020 ; Asimakis et al, 2021 ; Deguenon et al, 2021 ; He et al, 2021 ; Tegtmeier et al, 2021 ; Yu et al, 2021 ; Csorba et al, 2022 ; Li S. et al, 2022 ; Majumder et al, 2022 ; Wang et al, 2022 ). We have noticed with taken examples that Proteobacteria, Firmicutes and Actinobacteria were the most dominant phyla present in the insect gut could be due to their diverse roles in nutrition.…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%
“…The aphid displays colour races, pink and green, which show host plant preference (Via, 1999;Via et al, 2000), a differential response to predator and parasitoid pressure (Bálint et al, 2018), whilst these forms seemingly show differences related to their facultative or secondary endosymbiotic bacterial communities (Leclair et al, 2021). Recent research has also shown that R. maidis infesting maize grown in chemically treated (pesticides and herbicides) and untreated fields have a different facultative endosymbiont profile (Csorba et al, 2022). Since these endosymbionts, both the primary one (Buchnera aphidicola) and the secondary ones, which live in special cells called mycetocytes (bacteriocytes) in the body cavity of the aphid host adjacent to the ovarioles, are involved in supplying nutrients to the host aphid (essential amino acids) and vitamins, as well as protection against primary parasitic wasps (Hymenoptera: Braconidae) (cf.…”
Section: Effects Of Geographic Range: Insects As Exemplarsmentioning
confidence: 99%
“…Additional secondary symbionts reported from R. padi and R. maidis include S. symbiotica, H. defensa, R. insecticola, Rickettsia sp., Spiroplasma sp., Arsenophonus sp., and Wolbachia sp. [207,208]. Telesnicki et al [209] found a high frequency of infection with H. defensa in Argentinean M. dirhodum, which was mainly a host for R. insecticola in Chile [210].…”
Section: The Role Of Secondary Endosymbiontsmentioning
confidence: 99%